BEBERAPA SIFAT FISIS DAN KIMIA MINYAK BIJI SAGA LAUT (ADENANTHERA PAVONINA) - Gustan Pari; M Syachri (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The result of a study on some physical and chemical properties of saga laut seed oil prepared using pressing method is presented in this report.The result shows that the average value of moisture content,' boiling point, specific gravity, iodine number, acid number and saponification value respectively are 0,137 percent, 166, 7 degrees celcius, 0,939, 31.04, 10,33 and 166, 72. Properties of saga laut seed oil appear to be close to tengkawang oil.